2023
DOI: 10.1051/0004-6361/202244294
|View full text |Cite
|
Sign up to set email alerts
|

Peering into the young planetary system AB Pic

Abstract: Aims. We aim to revisit the formation pathway of AB Pic b, one of the first companions ever imaged straddling the exoplanet/browndwarf boundary. We based this study on a rich set of observations which allows us to investigate its orbital and atmospheric properties. Methods. We composed a spectrum of AB Pic b merging archival medium-resolution (R ∼ 4000) VLT/SINFONI K-band (1.96 -2.45 µm) data, with published spectra at J and H-bands from SINFONI, at Lp-band from Magellan-AO/CLIO2, and photometric measurements … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…However, this sample may be beneficial to explore the statistical distributions of spin-spin orientations between the host stars (i * ) and companions (i p ). A handful of obliquities have now been measured for individual brown dwarf companions and giant planets by combining rotation periods, radii, and projected rotational velocities (e.g., Bowler et al 2020b;Bryan et al 2020aBryan et al , 2021Zhou et al 2020;Palma-Bifani et al 2023), but larger samples are needed to assess the prevalence of stellar-companion spin-spin alignment in order to interpret this in the context of formation scenarios (e.g., Jennings & Chiang 2021). Companions to host stars with existing inclination constraints from this study may be promising targets for follow-up photometric monitoring and high-resolution spectroscopy in the future.…”
Section: Spin-spin Opportunitiesmentioning
confidence: 99%
“…However, this sample may be beneficial to explore the statistical distributions of spin-spin orientations between the host stars (i * ) and companions (i p ). A handful of obliquities have now been measured for individual brown dwarf companions and giant planets by combining rotation periods, radii, and projected rotational velocities (e.g., Bowler et al 2020b;Bryan et al 2020aBryan et al , 2021Zhou et al 2020;Palma-Bifani et al 2023), but larger samples are needed to assess the prevalence of stellar-companion spin-spin alignment in order to interpret this in the context of formation scenarios (e.g., Jennings & Chiang 2021). Companions to host stars with existing inclination constraints from this study may be promising targets for follow-up photometric monitoring and high-resolution spectroscopy in the future.…”
Section: Spin-spin Opportunitiesmentioning
confidence: 99%
“…However, constraining the formation history of VHS 1256 b using its atmospheric properties estimated from the forward-modeling approach remains challenging. A supersolar metallicity is usually used to quantify the solid material that is accreted during the formation, and the C/O is considered as a tracer of the birth location of the planet (see Nowak et al 2020;Petrus et al 2021;Hoch et al 2022;Palma-Bifani et al 2023), but with this study, we have shown that the estimates of these commonly used tracers of formation were strongly dependent on the model and the spectral information used for the fit. Moreover, Mollière et al (2022) have demonstrated that the relationship between chemical abundances and the formation mechanisms described by the models (e.g., Öberg et al 2011) is more complex than initially anticipated, and it is dependent on various intricate parameters, particularly in the case of formation within a disk.…”
Section: Discussionmentioning
confidence: 81%
“…The imposition of these assumptions leads to a limited number of free parameters (<6), and the quality of the fit heavily relies on the quality of the models. The impacts of these systematic errors on the estimation of atmospheric properties have already been recognized for L and M spectral types (Cushing et al 2008;Stephens et al 2009;Bonnefoy et al 2014;Manjavacas et al 2014;Lachapelle et al 2015;Bayo et al 2017;Petrus et al 2020Petrus et al , 2023Suárez et al 2021;Lueber et al 2023;Palma-Bifani et al 2023). These studies have interpreted these discrepancies as indications of a deficiency in the modeling of dust and haze within the synthetic atmosphere models.…”
Section: Introductionmentioning
confidence: 97%
“…We report the predictions of these models in terms of iso-mass (red-yellow lines) and iso-temperature (gray lines) curves as a function of R and log(g) for different ages (see Fig. 3), as done previously in Palma-Bifani et al (2023). A way to interpret the curves in Fig.…”
Section: Evolutionary Modelsmentioning
confidence: 95%
“…ForMoSA is a Bayesian forward-modeling code based on a nested sampling algorithm performing parameter exploration given a likelihood function (Skilling 2006). A full description of the code and applications on planetary-mass companions can be found in Petrus et al (2021) for HIP 65426 b, in Petrus et al (2023) for VHS 1256 AB b, and in Palma-Bifani et al (2023) for AB Pic b. Here we exploit its capabilities for studying the atmosphere of a companion at low spectral resolution (R λ ∼ 30).…”
Section: Formosamentioning
confidence: 99%